Measuring competitiveness - J. Peter Neary (University College Dublin, UCD School of Economics, 2005)
This paper reviews alternative approaches to measuring an economys cost competitiveness and proposes some new measures derived from the economic theory of index numbers. The indices provide a theoretical benchmark for estimated real effective exchange rates, but dier from standard measures in that they are based on marginal rather than average sectoral shares in GDP or employment. The use of the new indices is illustrated by some simple calculations which highlight the potential exposure of the Irish economy to fluctuations in the euro-sterling exchange rate.
hdl:10197/1314
Keywords: F40; C43; 330; competitiveness; economic theory of index numbers; European Monetary Union (EMU); real effective exchange rates (REERs); Internationaler Wettbewerb; Messung; Lebenshaltungskosten; Kaufkraftparität; Theorie; Indexberechnung